Auditor-Firm Conflict: Theoretical Concepts Application and Analysis of the Power Dynamics Involved - Eferakeya, idowu (Journal of Accounting Auditing and Business, 2024)
This study undertakes a theoretical analysis of the auditor-firm conflict. It relied on  the review of literature methodology  contextualized on  auditor’s appointment ,  firm economic pressure , management bargaining power, auditor’s fear of losing a firm, firm’s management economic power over the auditor, auditor’s personal attributes and moral reasoning, auditor’s tenure, audit fees, audit market competitiveness, non-audit services, audit firm size and the firm’s financial condition. The study relied on Goldman and Barlev model, exchange and dependency theories to explain the likely power positions in the auditor-firm relationship. Deductively the study based on the contexts indicated the presence of an asymmetry power structure where the auditor and firm have low and high power positions. The study however, proffered resolution measures such as reputational and litigation costs; strengthening of audit committees; control over auditor’s appointment and remuneration; effective discipline of firms and auditors and strong enforcement of standards. The measures can curtail the auditor’s and firm actions in reducing violation of auditing standards; improving auditor’s independence, reduce the firm’s pressure on the auditor and bring about balance of power positions. The paper has implications for understanding the auditor-firm conflict situation and provides opportunities for strengthening audit policy and audit standards development.